The association between the body roundness index and the risk of chronic kidney disease in US adults - Zhang, Jiaying; Yu, Xiaofeng (Frontiers in Medicine, 2024)
AimWe aimed to systematically assess whether the level of body roundness index (BRI) is associated with the risk of developing chronic kidney disease (CKD) in US adults.MethodsThe studied data was extracted from the National Health and Nutrition Examination Survey (NHANES) spanning from 1999 to 2018. A total of 29,062 participants aged ≥20 years with complete information about BRI and CKD were included in this study. Logistic regression analysis, multivariate linear regression analysis, restricted cubic spline (RCS) plots curve, stratified analysis and receiver operating characteristic (ROC) curve were performed to investigate the association between BRI and CKD.ResultsA total of 29,062 patients were included, involving 4,623 individuals with CKD and 24,439 individuals without CKD. A higher BRI level was substantially related to an increased prevalence of CKD in US adults. After adjusting for confounding variables, the BRI in the fourth quartile was correlated to a higher CKD prevalence (OR: 1.36; 95% CI: 1.10–1.70) compared to the lowest quartile. After adjusting for confounding variables, the BRI in the fourth quartile was correlated to a higher CKD prevalence (OR: 1.36; 95% CI: 1.10–1.70) compared to the lowest quartile. However, in the subgroup analysis stratified by race and body mass index (BMI), no significant associations between BRI and CKD were observed among Mexican participants (OR: 1.10; 95% CI: 0.98–1.23) and those with underweight or normal weight (OR: 0.95; 95% CI: 0.81–1.05). Moreover, a non-linear relationship was found between BRI and the prevalence of CKD. In ROC analysis, BRI demonstrated higher discriminating for CKD (area under the curve: 0.6247; 95% CI: 0.6161–0.6333; optimal cutoff value: 5.161) compared with other indices.ConclusionIn summary, BRI was independently associated with a higher prevalence of CKD in overweight and obese US adults, excluding Mexican. This may be an important therapeutic target and predictor of CKD. Physicians should advise patients with high BRI scores, especially overweight and obese patients, to embrace healthy lifestyle changes, such as maintaining a balanced diet and engaging in regular physical activity. These changes can help them control their body weight and reduce abdominal fat, ultimately lowering the risk of CKD.